Retrospective analysis of the cholesterol levels in a European mid-latitude population between 2007 and 2018: controversies and therapeutic implications - Ferrari, Davide; Motta, Andrea; Strollo, Marta; Locatelli, Massimo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Coronary heart disease is the leading cause of morbidity and mortality in developed countries and its association with LDL-cholesterol has been well established. During the last decades statin therapy, and an healthy lifestyle, has proven highly effective in reducing cardiovascular event rates. Yet, there is still controversy among national guidelines and clinical practice with regard to LDL-cholesterol measurements. The aim of this study was to verify whether significant changes in cholesterol levels were observed over a relatively long (12 years) period. We also compared the Friedewald-calculated with directly-measured LDL cholesterol in order to verify whether the two methods were equivalent. Methods: We retrospectively analyzed 288000 data (total cholesterol, HDL, LDL both directly-measured and Friedewald-calculated, and triglycerides), from 57600 individuals, collected at the San Raffaele Hospital in Milan between 2007 and 2018. Data were statistically analyzed using a linear regression over the 12 years long period of time. Results: We observed a general decreasing trend in total cholesterol (and an increasing trend in HDL) and a decrease in triglycerides only in the male group. Directly-measured  LDL did not correlate well with calculated LDL. Conclusion: The total cholesterol decrease and the corresponding increment in HDL was attributed to either an increased use of statin and/or an improvement of the general population dietary habits. The latter was further confirmed by the decrease in triglycerides observed in the male group. Based on our data, an alternative method for assessing atherogenics lipoproteins level has been proposed.